Delayed Speech in Children as a Symptom; Socio-demographic Features and Accompanying Clinical Diagnosis - Damla Eyuboglu; Murat Eyuboglu (Bilişsel Davranışçı Psikoterapi ve Araştırmalar Dergisi)
Delayed speech is a common clinical sign in children, and its prevalence has been determined to be 315%. The aim of this study was to review the clinical diagnosis of children with delayed speech who were referred to the pediatric psychiatry clinic and conduct a comparative study on the diagnostic groups in terms of their sociodemographic characteristics. The present study included 207 children at 18-60 months who had delayed speech. For each child, a sociodemographic data form and the Childhood Autism Rating Scale (CARS) were completed; moreover, the Ankara Developmental Screening Inventory (ADSI) was applied to evaluate his/her general developmental and cognitive levels. In the study, 52 children (25.1%) were female and 155 (74.9%) were male. 99 (47.8%) of them were diagnosed with Language Disorders, 65 (31.4%) with Cognitive Development Delays and 43 (20.8%) with Autism Spectrum Disorder. The incidence of perinatal complication history was determined at the highest level in the Cognitive Development Delay group. The time used for electronic media was high in each diagnostic group, but highest in the autism group. When the number of languages used by the mothers is compared, the mothers in Language Disorder group use more than one language in daily life. Delayed speech is a sign that may be accompanying with several clinical diagnoses. Early diagnosis and educational support programs may contribute to the healthy development of these children. [JCBPR 2019; 8(1.000): 43-50]